Některé aspekty financování rozvoje venkova - Zilvar, Josef (Univerzita Pardubice, 1998)
This article describes problems of finance a little economic activities in the country. It refers to problems inception savings and credits co-operatives.
Keywords: venkov; družstevní záložny; etické kodexy